G254(P) Can eating disorders in children and young people permanently affect growth and pubertal development?. (May 2019) - Neale, J; Pais, S; Nicholls, D; Hudson, L
Abstract : Aims: We aimed to assess what evidence there is that eating disorders in children and young people affect growth and puberty and to what extent this is permanent. Whilst a number of studies on long term physical sequelae of eating disorders in children and young people exist, reports are conflicting, and this literature has never been systematically reviewed. Methods: We systematically reviewed the literature using Pubmed, Embase, PsycINFO and Web of Science to search for studies which looked at the effects of growth and development in participants<18 years with an eating disorder. Results: Of 10 404 abstracts, we retrieved 96 articles and included 28 studies. Both cross-sectional and longitudinal studies were identified. Most individual studies were small (included <100 participants). Although we found evidence that eating disorders in children and young people are associated with impaired growth and delayed puberty compared to control groups, meta-analysis suggested no significant difference in stature. Impact on growth was found to be permanent in some studies. However, there was a larger body of evidence to suggest that catch-up growth is possible, with weight gain contributing to an acceleration of growth and final adult heights which were not significantly different from controls. In the majority of studies, pubertal delay was not seen at follow up. Conclusion: Children and young people with eating disorders are at risk of permanent effects on growth and reduced final height, though many will have the potential for catch up thus avoiding final stunting. Children and young people with eating disorders should have their growth and physical development regularly reviewed and monitored, and restoration of growth should be a goal in treatment to allow for catch up and prevent stunting. The potential effects on growth should be discussed with patients and their families.